부산·경남지역 노인의 구강보건행동과 주관적 구강건강인식도 조사 - 장경애; 김동열 (Han'guk Ch'iwisaeng Hakhoe chi, 2008)
The purpose of this study was to compare the oral health status of elderly people living in nursing home with private home in Busan, Kimhae and Jinju in Gyeongnam province for development oral healthy policy of elderly people. 253 elderly subjects aged more than 65 in a hall for the aged and special medical treatment hospital are made up questions. The date was analysed using the SPSS 13.0 program. The obtained result were as follows. 1. 39.5 percent elder people recognize that their subjective oral health is not good. In the case of above three times in brushing tooth a day, 29 percent people are less their oral health is good. As the number of times of brushing tooth decreases, the percent feeling their oral status good decrease(p<.05). 2. The respondents who have visited the dentist within one year are less than people with no visit. Also the percent having a mind that their oral health status is good is higher in the respondents having scaling than them without scaling(p<.05). The respondents who answer that their diet is not bad is most in the ratio of people feeling subjective oral health status good(p<.001). 3. The portion of people feeling their oral status not healthy is highest in the respondents without tooth(p<.05). 4. Among the respondents answering their subjective oral health is not good, the some problem of conversation due to no tooth or denture and relation with others is issued each(p<.001). This study suggests that perceived toothbrusing frequency and periodic scaling with oral health among the elderly. The findings of this study will be helpful to policy makers to design plants to increase the oral health related quality of life among the edlerly. KCI Citation Count: 5